PENGARUH KETEBALAN TERHADAP KEKUATAN PANEL KACA - Fridha Nurrahma; Muryanti Muryanti; Ilham Nurhuda; Han Ay Lie (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
This research aimed at investigating the effect of glass thickness on the strength of annealed glass panels. The research was conducted using both experimental tests and numerical simulations. The experimental tests were conducted using the double ring method, while the numerical simulations were carried out using Finite Element Method (FEM). Numerical simulations were conducted first to determine efficient meshing, dimension of the specimen, and the equipment capacity. The number of specimens were 400 with the same width and length of 200 mm x 200 mm. The thickness of which were varied from 3 mm up to 10 mm. The test results were maximum load and fracture origin. Both of these results were used to calculate the strength of the glass that was expressed as failure stress at the location of fracture origin. The failure stress scattered in a wide range, hence statistical analysis was required to analyze the glass strength. From the analysis, it can be seen that the strength of glass was affected by its thickness. Some graphs have been created to show the allowable pressure that can be resisted by certain dimension of glass panels.